Identification and Phenotyping of Leukocytes in Bovine Bronchoalveolar Lavage Fluid - Soethout, E. C. (American Society for Microbiology, 2004)
A method is proposed to identify leukocyte subpopulations in bovine bronchoalveolar lavage fluid by dual-laser flow cytometry. The technique uses several parameters, i.e., exclusion of highly autofluorescent alveolar macrophages and inclusion of leukocytes on the basis of labeling by specific antibodies and light scatter characteristics.